Planets - Berger, Melvin; Berger, Gilda (New York : Scholastic, 2010)
Contains twenty true or false questions about the planets of the solar system, with full-color photographs.
Includes index.
4.1
K-3
Keywords: Planets -- Miscellanea -- Juvenile literature; Planets; Questions and answers; Planets -- Miscellanea; Questions and answers